Translating Migrations, (Re)Presenting Cultures in Transit: Licia Canton’s “The Motorcycle” - Marino, Luisa (Italian Canadiana)

(untitled) (Iter Press, 2020)
This essay investigates the relationship between the idea of movement and the concept of translation in Licia Canton’s short story “The Motorcycle” and in its Italian translation. The essay looks at translation both as a metaphor of negotiation and mediation that bridges two linguistic and cultural backgrounds and as a process thanks to which a text can effectively circulate in several languages and cultures. Thanks to some excerpts taken from the Italian text, the issue of the accent, that of self-translation and identity are explored through the lens of language, underlining its role in shaping and conveying images and narratives of the migrant.